Authentic Participation for Territorial Public Management: A Challenge for Citizens and Government - Rivera Ángel, Fredy Alexis (2022)
In this article, we intend to discuss the need to identify when authentic participation exercises are involved in public planning and management to differentiate these exercises from others where manipulation and legitimation purposes are at the order of the day. Documentary and bibliographic research was conducted to deeply study the characteristics necessary to achieve authentic participation. With the help of categories or steps that include the requirements of what authentic participation should be, advanced exercises can be identified for those who are not even participating. The people must react and seek greater decision-making power to not let others decide the future of everyone in truly authentic planning and public management exercises to which this article is intended to contribute.